2016
DOI: 10.1007/s11482-016-9449-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Predicts Survival and Hospitalisation in a Heart Failure Portuguese Population

Abstract: The aim of this study was to examine whether quality of life (QoL) is an independent predictor of death and hospitalization for cardiovascular (CV) causes in patients with heart failure (HF). A 6-year prospective study was conducted on 130 outpatients with HF who were recruited from a cardiology service at S. João Hospital. Generic QoL was measured with the Medical Outcome Study 36-item Short Form Survey (SF-36), disease-specific QoL was measured with the Kansas City Cardiomyopathy Questionnaire (KCCQ) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Numerous prospective studies have demonstrated the ability of various quality of life (QOL) scores to predict mortality in patients with heart failure [41-43], but often employ lengthy scoring systems. Some of these studies have been criticized for not adjusting for covariates [42].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous prospective studies have demonstrated the ability of various quality of life (QOL) scores to predict mortality in patients with heart failure [41-43], but often employ lengthy scoring systems. Some of these studies have been criticized for not adjusting for covariates [42].…”
Section: Discussionmentioning
confidence: 99%
“…The second level is formed by quality of life, which is an influencing variable and as such a predictor of some influenced variables. Quality of life is a predictor of health [11][12][13], depression [14] and the outcome of the Czech presidential election [15]. Predictors of quality of life need to be distinguished from factors supporting its improvement [16].…”
Section: Introductionmentioning
confidence: 99%
“…In others words, using the QALY model as the measure of effectiveness in economic evaluations implies missing temporary changes in utility, particularly when these changes are due to disease-related events. For instance, when having access to two consecutive utility measurements with the same value – one before and other after a particular event –, using the QALY model leads to an implicit assumption that the utility of that same patient was constant throughout both time points and that the event that took place had no influence in the QoL of that patient, even though this assumption is unlikely to hold in an event such as a hospitalisation [ 10 , 11 ]. In this sense, empirical identification of the direct impact of hospitalisation on the change in utility could provide an interpretation for some of the unexplained variance in QoL responses in clinical practice and clinical trials, as well as it may provide assistance to researchers in designing trials aimed at assessing patient-reported outcomes.…”
Section: Introductionmentioning
confidence: 99%